2021
DOI: 10.1039/d0sc04069j
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative activating effects of metal ion and Brønsted acid on a metal oxo species

Abstract: Metal oxo (M=O) complexes are common oxidants in chemical and biological systems. The use of Lewis acids to activate metal oxo species has attracted great interest in recent years, especially...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Addition of Sc(OTf) 3 to 1 . Previous studies revealed that the adding of Lewis acid (i.e., Sc 3+ ion) not only stabilize the high‐valent metal–oxo species, but also affects their oxidizing capabilities 18–29 . Experimental results are seemingly simple; species 1 , which is unreactive, is still unreactive when adding Sc(OTf) 3 ( 1‐Sc ).…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…Addition of Sc(OTf) 3 to 1 . Previous studies revealed that the adding of Lewis acid (i.e., Sc 3+ ion) not only stabilize the high‐valent metal–oxo species, but also affects their oxidizing capabilities 18–29 . Experimental results are seemingly simple; species 1 , which is unreactive, is still unreactive when adding Sc(OTf) 3 ( 1‐Sc ).…”
Section: Methodsmentioning
confidence: 98%
“…The chemistry of these species has therefore been of great interest to the bioinorganic chemistry community during the past decades. Especially, redox‐inactive metal ions functioning as Lewis acids have pivotal roles in regulating the oxidizing capabilities of such metal–oxo species in many enzymatic and chemical transformations 18–29 . Previous studies have revealed that binding of a redox‐inactive metal ion can not only markedly change the reactivity, but also tune the valence tautomerization of the metal–oxo species 18,30–32 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Solid-state structures and extended X-ray absorption fine structure spectroscopy reported the binding of one or more Sc 3+ ions directly to the oxo moiety and the rate of ET was found to be correlated to the Lewis acidity of cations . The OAT process, catalyzed by Ru–, Fe–, or Mn–oxo complexes, was reported to be enhanced in the presence of redox-inactive metals. , Moreover, Cr, Fe, and Cu peroxo complexes were also shown to be affected by the additional cations; nucleophilicity, electrophilicity, and ET abilities were also shown to depend on the Lewis acidity of the redox-inactive metals. , With high-valent metal–oxygen intermediates, different reaction pathways can proceed concurrently, leading to low selectivity of the desired products . The addition of redox-inactive cations could potentially tune the oxidative reactivity and provide insights on designing more selective oxidation catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…High-valent transition-metal–oxygen intermediates are crucial in various biological and chemical oxidation processes, including hydrogen atom transfer (HAT), oxygen atom transfer (OAT), and electron transfer (ET). The water oxidation process in natural photosynthesis, for example, involves the oxygen evolving complex (OEC) which contains a Mn 4 CaO 5 cluster that forms Mn–oxygen intermediates during catalysis. The presence of Ca 2+ ions in the cluster has been proven to be crucial to the reactivity of OEC. This finding led to several recent studies on the effect of redox inactive metals toward the processes of HAT, OAT, and ET, as well as the nucleophilicity and electrophilicity of high-valent metal–oxygen intermediates. …”
Section: Introductionmentioning
confidence: 99%